Musik, ungdomsliv og sjæles frelse: Musik og tro i Københavns KFUM omkring år 1900 - Nissen, Peter E. (Kirkehistoriske Samlinger, 2007)
In this article, the history of the musical culture of Copenhagen’s Young Men’s Christian Association/YMCA (Kristelig Forening for unge Maend/KFUM) around 1900 is analyzed. The focus is on two central parts: the songs and the inauguration cantata. The first part is about the particular songs and community singing of the association. An ethnohymnological approach with focal point on the role of the hymns in the process of creating social community and identity shows how the songs become an important function for the identity of the organization. Under the leadership of the charismatic secretary Olfert Ricard, the content of the association’s hymn books changed from a pietistic Christianity to an open-minded assimilation of non-sacred culture. New songs by Ricard and his fellows focused mainly on youth culture and fellowship from the perspective of a young man. Jesus was regarded as the young man’s role model and hero. This inspiration was drawn from Anglo-American revivalism, as it emerged in the international YMCA, and was transformed into an ideology of a Christian national awakening among youngsters. The tunes of the songs were taken from well-known songs of the time. The symbolic content of the original song was by the melody transformed and carried over to the new song. This meant that the communication effect ofthe song’s message became even stronger and more familiar. For the same reason tunes of high emotional quality were present. The creation of new songs was an important part of making a strong spiritual bastion in Copenhagen. Music was seen as an important factor in the intermediation and education of the young men as good educated Christians. At the same time, music had a representative function. The music would show the abilities of the organization to the community outside. The second part is an investigation of the musical space around the performance of the cantata at the inauguration of the KFUM/YMCA head-quarters September 16th, 1900. It is an exploration of how the music promoted the association and its theology. The inauguration day was strongly representative in character and the stage was set for future identity and an ideal ‘liturgical practice’. The text of the cantata by Jacob Paulli focused on the importance of giving young men the right Christian upbringing and the value of having a place, where this could be done. The music is consistent with the musical ideals of the time: A moderate expressive character, which emphasizes the words. The male choir has an important role in the work, and it becomes a symbolic representation ofthe YMCA-leaders through warning texts to the young men and the representatives ofthe town. The cantata represents and integrates the emotional aspects of the new era of the association, which was confirmed by the description of the event in the local newspapers. The inauguration music was a part of the visual profiling of the association. Inspired by the grand houses of the Anglo-American YMCA, the Danish organization underlined visual presence. This was a part of the demonstration of the success of holiness, and Olfert Ricard took the lead in this achievement. Another important aspect of the music was the importance of becoming a part of the local educated culture in Copenhagen. Music of good quality was essential in the local students’ association, and the target group was partly the same. Ricard saw education and good taste as a crucial element in young men’s spiritual growing and the salvation of the nation; the music culture of the association should be an important part of achieving this goal. In their music making, the members of the YMCA of Copenhagen created a sacred place, similar to the churches. This was in line with the romantic music of the time, where the boundaries between sacred and profane were fluid. The contact with the society outside the association was strong, and the organization became an active member of the cultural war for the souls of the urban population. The First World War and the following cultural confusion and crisis ruined the dreams, and the decline of the organization began.